1989
DOI: 10.1111/j.1471-4159.1989.tb09206.x
|View full text |Cite
|
Sign up to set email alerts
|

Regional Distribution of Neuropeptide Y and Its Receptor in the Porcine Central Nervous System

Abstract: The regional distribution of neuropeptide Y (NPY) immunoreactivity and receptor binding was studied in the porcine CNS. The highest amounts of immunoreactive NPY were found in the hypothalamus, septum pellucidum, gyrus cinguli, cortex frontalis, parietalis, and piriformis, corpus amygdaloideum, and bulbus olfactorius (200-1,000 pmol/g wet weight). In the cortex temporalis and occipitalis, striatum, hippocampus, tractus olfactorius, corpus mamillare, thalamus, and globus pallidus, the NPY content was 50-200 pmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(4 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…NPY was over-expressed ( P -value < 8.1 × 10–4, fold change = 7.94) in neuroblasts relative to non-neuronal cells in GSE16855. This result is consistent with reports that the olfactory bulb exhibit high levels of immunoreactive NPY in the brain of pigs [65] and that NPY may inhibit excitatory neurotransmission in the rat olfactory bulb [66]. VEGFC was over-expressed in neuroblasts relative to non-neuronal cells ( P -value < 1.5 × 10 -9 , fold change > 10) in experiment GSE16855.…”
Section: Resultssupporting
confidence: 91%
“…NPY was over-expressed ( P -value < 8.1 × 10–4, fold change = 7.94) in neuroblasts relative to non-neuronal cells in GSE16855. This result is consistent with reports that the olfactory bulb exhibit high levels of immunoreactive NPY in the brain of pigs [65] and that NPY may inhibit excitatory neurotransmission in the rat olfactory bulb [66]. VEGFC was over-expressed in neuroblasts relative to non-neuronal cells ( P -value < 1.5 × 10 -9 , fold change > 10) in experiment GSE16855.…”
Section: Resultssupporting
confidence: 91%
“…Neuropeptide Y ( NPY) is a member of a family of pancreatic peptides, and it is widely distributed in the central nervous system ( CNS) and, in particular, the hypothalamus (Tatemoto, 1982;Busch-Sorensen et al, 1989). Immunocytochemical evidence demonstrated coexistence of NPY and norepinephrine in brain stem neurons that project to the hypothalamus.…”
Section: Neuropeptide Ymentioning
confidence: 99%
“…Moreover, in situ hybridization studies have revealed that the distribution of NPY mRNA correlates rather well with that of NPY-likeimmunoreactive material (Terenghi et al, 1987;Chan-Palay et al, 1988). Many studies have demonstrated the existence of specific receptors for NPY and related peptides in mammalian brain (Chang et al, 1985(Chang et al, , 1986(Chang et al, , 1988Saria et al, 1985;Martel et al, 1986Martel et al, , 1987Martel et al, , 1988Martel et al, , 1990aInui et al, 1988Inui et al, , 1989Busch-Sorensen et al, 1989;Lynch et al, 1989;Sheikh et al, 1989a,b;Ohkubo et al, 1990;Rosier et al, 1990;Sheikh and Williams, 1990;Dumont et al, 1992;Quirion and Martel, 1992). Using anatomical methods, it was shown that NPY binding sites are concentrated mostly in the hippocampal formation, various cortical areas, the olfactory bulb, and the lateral septum.…”
mentioning
confidence: 99%